The runaway king - Nielsen, Jennifer A. (Ascendance trilogy, 2013)
Young King Jaron has taken the throne of Carthya, but after enemies attempt to assassinate him, and a neighboring kingdom threatens invasion, he finds that he has no friends in the palace, not even his bride-to-be, princess Amarinda--and his regents think it would be better for Carthya if he just disappeared again.